The Book of Obadiah in the Septuagint - Strzałkowska, Barbara (Collectanea Theologica, 2021)
The Book of Obadiah, although short (it has only 21 verses; the shortest in the Hebrew Bible), is at the same time very difficult. The difficulties are manifested in its linguistic and textual layers, but above all in what concerns its content, theology and interpretation. The Greek translation of Obad contained in the LXX is particularly important because it represents a way of understanding the Book going back to pre-Christian, Hellenistic times, which strongly emphasised the theme of threats to Israel from other nations. In the Greek translation (LXXObad), the cursing character of the Book is radicalised and the guilt of the enemies (Edomites – Idumeans) is highlighted. The article presents the Book of Obadiah in its historical context (both the Hebrew original and the Greek version), and presents its text, content and character in the Septuagint version. It compares it with LXXJer 29 (LXX numbering) and shows how the challenging theology of the Book was understood among the Jews of Hellenistic Alexandria. The universalisation of the message of the Book by the LXX translation was later continued in its patristic and rabbinic interpretations.